Pengaruh Model Discovery Learning Berbantuan Canva terhadap Kemampuan Komunikasi Matematis Siswa SMP Negeri 2 Deli Tua - Maulidani Putri Rangkuti; Muliawan Firdaus (Jurnal Pustaka Cendekia Pendidikan, 2024)
This research aims to see whether there is an influence of the Discovery Learning model on students' mathematical communication skills with the help of Canva as a learning video. This research is included in the quasi-experimental category with a one group pretest-posttest research design. The population in this study were all class IX students of SMPN 2 Deli Tua T.A 2023/2024 with a sample of class IX-4 as the experimental class selected using the cluster random sampling method. The test instruments used in this research are pretest and posttest in the form of presentations which are used to determine students' mathematical communication abilities. Based on the simple linear regression hypothesis test analysis carried out by carrying out prerequisite tests first, the value was obtained, namely which resulted in being accepted, which means that the Canva-assisted Discovery Learning model has a significant influence on students' mathematical communication skills. The magnitude of the influence of the Discovery Learning model with the help of Canva on the mathematical communication skills of students in class IX of SMPN 2 Deli Tua is 64,5% which is calculated through the determinant coefficient test. Factors in the Discovery Learning model learning process cause an influence on students' mathematical communication skills. So the magnitude of the influence of the Discovery Learning model on students' mathematical communication skills is also obtained.